Development Prospects of Transportation in the Agroindustrial Complex by Reducing the Damage of Fruit and Vegetable Products When using the Pneumatic Container - N.V, Byshov; S.N, Borychev; I.A, Uspenskiy; A.V, Shemyakin; I.A., Yukhin; D.A, Fedyashov; I.A, Piskachev (International Journal of Engineering and Technology, 2018)
The aim of the study is to reduce damage to potatoes in the body of vehicles when placed in containers for intrafarm transportation due to the development of new science-based technical solutions. Research methods are theoretical studies performed on the basis of laws and methods of theoretical mechanics. The task of the study is to determine the damage of potatoes when conducting laboratory tests on a shaker table that simulates the movement of a vehicle. The shaker table is a control unit, an installation that generates a reciprocating motion and a platform attached to the installation, which produces oscillatory movements of specified parameters. When imitating the movement of a vehicle, the following parameters were set: platform oscillation frequency from 6 Hz to 10 Hz, with increment of 2 Hz; the oscillation speed of the cargo platform from 1.8 m / s to 3.0 m / s, with 0.6 m / s increment and platform oscillation amplitude of 20 mm. Each stage of the experiment lasted for 2 minutes. According to the results of the experiment and the analysis of the damage to potatoes, the values of damage were obtained, which do not go beyond the maximum permissible agrotechnical requirements of 5 %, with the maximum specified vibration parameters. The results of the experiment suggest that the use of a pneumatic container leads to a decrease in the damage of potatoes when the vehicle is moving along a micro-profile of field roads. When using this pneumatic container, the share of damaged products decreases by 0.6-1.1 % with an increase in the vehicle speed by 1.7 times.Â Â Â